A comparative study on the properties of chromium coatings deposited by magnetron sputtering with hot and cooled target. (September 2017) - Sidelev, D.V.; Bleykher, G.A.; Bestetti, M.; Krivobokov, V.P.; Vicenzo, A.; Franz, S.; Brunella, M.F.
Abstract: This article reports on the analysis of energy flux density to the substrate and results of the detailed study of properties of Cr coatings deposited by magnetron sputtering with hot and cooled Cr targets. It was demonstrated that deposition rates of Cr films increase and particle flow density on the substrate changes by target sublimation. Heat radiation of the hot target leads to more rapid heating of the substrate and this energy flux has a main contribution in enhancement of total energy flux density on the substrate (from 0.06 to 0.43 W/cm 2 ). As consequence, energy per deposited atom increases in 5.8 times for the hot Cr target sputtering even taking into account higher deposition rates. Cr films deposited by the cooled target sputtering have a (110) crystal texture, columnar microstructure, low surface roughness (∼2.66 nm) and hardness from 13.8 to 14.2 GPa. In the case of the hot target sputtering, the competitive crystal growth of (110) and (200) directions is observed, microstructure of the Cr films is denser and homogeneous, grain size increases up to 200–300 nm and film surface becomes coarse ( R a ∼11.75 nm), hardness of the Cr films drops by a factor of about 2. Highlights: Cr films were deposited by cooled and hot Cr target sputtering. Increased heat flux on the substrate (7 times) due to target heat radiation. The target state influences on the crystal structure and film morphology. The film hardness depends on substrate temperature and film thickness.